Early stages of divergence: phylogeography, climate modeling, and morphological differentiation in the South American lizard Liolaemus petrophilus (Squamata: Liolaemidae) - Fontanella, Frank M. (2012)
This study examines the phylogeographic structure within the Patagonian lizard Liolaemus petrophilus and tests for patterns of between-clade morphological divergence and sexual dimorphism as well as demographic and niche changes associated with Pleistocene climate changes. We inferred intra-specific relationships, tested hypotheses for historical patterns of  population expansion, and incorporated ecological niche modeling (ENM) with standard  morphological and geometric morphometric analyses to examine between-clade divergence as indirect evidence for adaptation to different niches. The two inferred haploclades diverged during the early Pleistocene with the Southern clade depicting the genetic signature of a recent population increase associated with expanding niche envelope, whereas the Northern clade shows stable populations in a shrinking niche envelope. The combination of molecular evidence for post-isolation demographic change and ENM, suggest that the two haploclades have responded differently to Pleistocene climatic events.